2021
DOI: 10.1007/s10903-021-01211-w
|View full text |Cite
|
Sign up to set email alerts
|

Is Medicine Just a DREAM for DACA Students? DACA Practices and Policies Among U.S. Medical Schools

Abstract: As of 2020, 75 accredited institutions with the Association of American Medical Colleges (AAMC) are described as "DACAfriendly" and welcome undocumented students to apply under the Deferred Action for Childhood Arrivals (DACA) program. However, there is wide variation in their DACA policies, complicating an already demanding application process. Herein, we discuss this process and the common challenges for DACA-recipients. From September 2018 to July 2019, a three-item survey was emailed to admissions represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(6 reference statements)
1
3
0
Order By: Relevance
“…Our study also supports previous studies which have found that fundamental immigration policy may not be known to key educators and stakeholders [ 21 ]. This pilot was focused on advisors who directly work with students entering medical education, however, even more important may be awareness of immigration policy among medical education and healthcare leadership.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study also supports previous studies which have found that fundamental immigration policy may not be known to key educators and stakeholders [ 21 ]. This pilot was focused on advisors who directly work with students entering medical education, however, even more important may be awareness of immigration policy among medical education and healthcare leadership.…”
Section: Discussionsupporting
confidence: 91%
“…Past programming efforts for students who are undocumented, DACA recipients, or on a student visa have primarily focused on providing information to learners [ 19 , 20 ], despite gaps in knowledge among medical educators and administration [ 21 , 22 ]. Thus, we saw an opportunity for targeting individuals who advise students who are undocumented, DACA recipients, or on a visa.…”
Section: Introductionmentioning
confidence: 99%
“…In the aftermath of the rescission, the Association of American Medical Colleges (AAMC) filed an amicus brief in 2018 on behalf of 33 leading health organizations renouncing the rescission that would have affected ~ 30,000 health care workers [ 7 ]. Other professional organizations like the American Nurses Association, American Psychological Association, and National Association of Social Workers strongly renounced the rescission, called for removal of barriers to professional licensure, and held trainings in how to support DACA recipients [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Even before the pandemic, there was increasing recognition of unique barriers DACA recipients faced in pursuing medical education [ 11 ], including that schools may only accept state residents (which DACA recipients are not always recognized as), prioritize their own in-state residents, and offer little to no financial support for a population ineligible for federal aid [ 12 ]. By 2020, 75 accredited medical schools were deemed “DACA friendly,” though varied in their policies [ 7 ]. Post-graduation, DACA recipients face complications in the medical licensure process, particularly since eligibility is governed by states, with only five allowing undocumented immigrants full access [ 11 , 13 ].…”
Section: Introductionmentioning
confidence: 99%